Hubungan Antara Kecerdasan Emosional dengan Hasil Belajar Peserta Didik Pada Mata Pelajaran Biologi - Salimah, Khansa Nurul; Suharsono; Egi Nuryadin (Jurnal Pendidikan Biologi Undiksha, 2023)
This study aims to determine the relationship between emotional intelligence with student learning outcomes in biology subject. The method used in this research is correlational quantitative. The population of this study was all 8 classes of XI MIPA SMA Negeri 1 Tasikmalaya for the academic year 2022/2023 and the sample used were class XI MIPA 2 and XI MIPA 3 with 63 students taken by purposive sampling technique. The instrument used in this study was an emotional intelligence questionnaire adapted from The Schutte Self Report Emotional Intellegence Test (SSEIT) with 26 statements consisting three indicators including appraisal and expression of emotion, regulation of emotion, and utilization of emotion. While the data on learning outcomes is measured on the cognitive aspect using the midterm assessment scores obtained from the biology teacher in class XI MIPA SMA Negeri 1 Tasikmalaya. This study uses data analysis statistical pearson bivariate correlation test. The result of the study show that there is a relationship between emotional intelligence with student learning outcomes in biology subject in class XI MIPA SMA Negeri 1 Tasikmalaya for the academic year 2022/2023 positively and significantly with a correlation coefficient of 0,632 which the relationship is in the strong category. Keywords: Emotional Intelligence; Learning Outcomes; Students